2021
DOI: 10.1177/10497323211020290
|View full text |Cite
|
Sign up to set email alerts
|

“Now I Am Myself”: Exploring How People With Poststroke Aphasia Experienced Solution-Focused Brief Therapy Within the SOFIA Trial

Abstract: Aphasia, a language disability, can profoundly affect a person’s mood and identity. The experiences of participants who received Solution-Focused Brief Therapy, a psychological intervention, were explored in the Solution-Focused brief therapy In poststroke Aphasia (SOFIA) Trial. Thirty participants with chronic aphasia, 14 with severe aphasia, participated in in-depth interviews that were analyzed using framework analysis. Two overarching themes emerged: valued therapy components (exploring hopes, noticing ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
3
4
0
Order By: Relevance
“…This is consistent with the need for clinicians to ensure that people with aphasia are included in therapy goal setting and provided with communication support to make choices, negotiate, and agree upon goals and therapy activities [38]. This finding is consistent with solution-focused brief therapy, which views participants as the experts in their lives and enables them to achieve their goals and outcomes by drawing on their strengths, skills, and resources [39]. Furthermore, in the current study, the working relationship with the experienced therapist was highly valued and important to participants.…”
Section: Discussionsupporting
confidence: 71%
“…This is consistent with the need for clinicians to ensure that people with aphasia are included in therapy goal setting and provided with communication support to make choices, negotiate, and agree upon goals and therapy activities [38]. This finding is consistent with solution-focused brief therapy, which views participants as the experts in their lives and enables them to achieve their goals and outcomes by drawing on their strengths, skills, and resources [39]. Furthermore, in the current study, the working relationship with the experienced therapist was highly valued and important to participants.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, support provided by peers, family, and those with similar experiences of concussion has been found to be particularly meaningful to students following injury [ 39 ]. Individuals who receive appropriate education about management techniques and feel more supported post-concussion experience fewer symptoms and recover more quickly [ 7 , 40 ]. Peer mentoring targets these modifiable aspects of the neurobiopsychosocial model of concussion, directly addressing how students understand, think about, and act on their injury experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of peer-led education show that peers like talking to other peers as well, often reaching out to peers before medical, sport, or educational professionals [ 34 , 39 ]. Serving as a mentor builds interpersonal skills and confidence that can translate to solving problems beyond college as well [ 27 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, participants reported that not all nursing homes in Singapore provide physical therapy or rehabilitation on a regular basis. And when the services are provided, these are physiotherapy and occupational therapy that are “usually more for maintenance.” A recent study demonstrated that poststroke psychological therapy could facilitate the renegotiation of poststroke identity for people who experience aphasia (Northcott et al, 2021). Crucially, this suggests there is room for improving the well-being of poststroke people, and that the goal of therapy should not be limited to maintenance only.…”
Section: Resultsmentioning
confidence: 99%